2005
DOI: 10.1002/mrd.20301
|View full text |Cite
|
Sign up to set email alerts
|

Actions of progesterone on uterine immunosuppression and endometrial gland development in the uterine gland knockout (UGKO) ewe

Abstract: In ewes, the uterine gland knockout (UGKO) phenotype is caused by neonatal exposure to norgestomet to arrest uterine gland development and produce an adult which has a uterus characterized by the lack of endometrial glands. Since endometrial glands in the sheep produce the lymphocyte-inhibitory protein, ovine uterine serpin (OvUS), an experiment was conducted with ewes of the UGKO phenotype to evaluate whether the inhibitory actions of progesterone on tissue rejection responses in utero are dependent upon the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 49 publications
(50 reference statements)
0
21
0
Order By: Relevance
“…Pregnant endometrium was obtained from cow (Bos taurus; Day 100), mare (Equus cabalus; Day 59), bitch (Canis lupus familiaris; Day 60), rhesus monkey (Days 36 and 37), and rat (Day 10.5). Also, uteroplacental tissue from a pregnant mouse (Day 14) as well as intercaruncular endometrium from an ovariectomized ewe (Ovis aries) treated with 100 mg of progesterone for 60 days [20] were also included in the present study. Quality and concentration of the total RNA collected were determined spectrophotometrically.…”
Section: Reverse Transcription-polymerase Chain Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pregnant endometrium was obtained from cow (Bos taurus; Day 100), mare (Equus cabalus; Day 59), bitch (Canis lupus familiaris; Day 60), rhesus monkey (Days 36 and 37), and rat (Day 10.5). Also, uteroplacental tissue from a pregnant mouse (Day 14) as well as intercaruncular endometrium from an ovariectomized ewe (Ovis aries) treated with 100 mg of progesterone for 60 days [20] were also included in the present study. Quality and concentration of the total RNA collected were determined spectrophotometrically.…”
Section: Reverse Transcription-polymerase Chain Reactionmentioning
confidence: 99%
“…Aliquants of purified pig ACP5 [22] and uterine flushing from an ovariectomized ewe treated with corn oil (the vehicle for progesterone) for 60 days were included as positive and negative controls, respectively. Western blot analysis was performed as described elsewhere [20] with minor modifications. Briefly, the blocking and incubation buffer was TBS-T (10 mM Tris [pH 7.6], 0.9% [w/v] NaCl, and 0.3% [v/v] Tween-20) that contained 5% (w/v) nonfat dry milk.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…It has been reported that the interferon‐stimulated gene 15 kDa protein (ISG15) is expressed in the uterus (Johnson et al, ), CL, blood cells (Oliveira et al, ), and bone marrow (Yang, Liu et al, ) during early pregnancy in sheep, which is induced by the IFNT through an endocrine manner in sheep (Bott et al, ). Furthermore, the IFNT modifies the maternal immune system to adapt to the presence of a fetal allograft in sheep and cattle (Padua, Tekin, Spencer, & Hansen, ; Skopets, Li, Thatcher, Roberts, & Hansen, ; Walker et al, ). Lymph nodes spread throughout the lymphatic system and are the sites where the immune reaction or suppression takes place (Buettner & Bode, ).…”
Section: Introductionmentioning
confidence: 99%
“…A central mechanism to protect the conceptus before implantation is attributed to the immunesuppressive actions of progesterone (P 4 ). For example, P 4 delays rejection of an allograft transplanted in the uterus of ovariectomised P 4 -treated ewes (Padua et al 2005).…”
Section: Introductionmentioning
confidence: 99%